Visualizing microtubule structural transitions and interactions with associated proteins - Nogales, Eva; Zhang, Rui (Current opinion in structural biology, 2016)
•Progress in cryo-EM resolution now allows building atomic models into microtubule (MT) maps.•GTP hydrolysis induces strain in α-tubulin at longitudinal interfaces between dimers.•MAPs bind either at intra or interdimer contacts, the latter are sensitive to MT nucleotide state.•Cryo-EM studies have led to models of kinesin/dynein mechanochemistry on MTs.•Disorder-to-order transitions guide β-tubulin tail to the active site of its glutamylase. Microtubules (MTs) have been the subject of cryo-electron microscopy (cryo-EM) studies since the birth of this technique. Although MTs pose some unique challenges, having to do with the presence of a MT seam, lattice variability and disorder, MT cryo-EM reconstructions are steadily improving in resolution and providing exciting new insights into MT structure and function. Recent work has lead to the atomic-detail visualization of lateral contacts between tubulin subunits and the conformational changes that give rise to strain in the MT lattice accompanying GTP hydrolysis. Cryo-EM has also been invaluable in describing the interactions between MTs and MT associated proteins (MAPs), which function to regulate MT dynamic instability, move cargoes, or contribute to other MT cellular processes.